Visceral Leishmaniasis Urbanization in the Brazilian Amazon Is Supported by Significantly Higher Infection Transmission Rates Than in Rural Area - Rodrigo R. Furtado; Ana Camila Alves; Luciana V. R. Lima; Thiago Vasconcelos dos Santos; Marliane B. Campos; Patrícia Karla S. Ramos; Claudia Maria C. Gomes; Márcia D. Laurenti; Vânia Lucia da Matta; Carlos Eduardo Corbett; Fernando T. Silveira (Microorganisms, 2022)
This was an open cohort prospective study (2016–2018) that analyzed the prevalence and incidence rates of human Leishmania (L.) infantum chagasi-infection and the evolution of their clinical-immunological profiles in distinct urban and rural scenarios of American visceral leishmaniasis (AVL) in Pará State, in the Brazilian Amazon. These infection profiles were based on species-specific DTH/IFAT-IgG assays and clinical evaluation of infected individuals, comprising five profiles: three asymptomatic, Asymptomatic Infection [AI], Subclinical Resistant Infection [SRI], and Indeterminate Initial Infection [III]; and two symptomatic, Subclinical Oligosymptomatic Infection [SOI] and Symptomatic Infection [SI = AVL]. The two distinct scenarios (900 km away) were the urban area of Conceição do Araguaia municipality and the rural area of Bujaru municipality in the southeast and northeast of Pará State. Human populations were chosen based on a simple convenience sampling design (5–10% in each setting), with 1723 individuals (5.3%) of the population (32,464) in the urban area and 1568 individuals (8.9%) of the population (17,596) in the rural one. A serological survey (IFAT-IgG) of canine infection was also performed in both scenarios: 195 dogs in the urban area and 381 in the rural one. Prevalence and incidence rates of human infection were higher in the urban area (20.3% and 13.6/100 person-years [py]) than in the rural setting (14.1% and 6.8/100-py). The AI profile was the most prevalent and incident in both urban (13.4% and 8.1/100-py) and rural (8.3% and 4.2/100-py) scenarios, but with higher rates in the former. An III profile case evolved to SOI profile after four weeks of incubation and another to SI (=AVL) after six. The prevalence of canine infection in an urban setting (39.2%) was also higher (p < 0.05) than that (32%) in the rural zone. AVL urbanization in Pará State, in the Brazilian Amazon, has led to infection rates significantly higher than those in rural sites, requiring more intense control measures.